PUBLIC PERCEPTION OF MARITAL RAPE IN YOGYAKARTA: STUDY QUALITATIVE METHOD - Denalian, Fatimmah; Besral, Besral (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2024)
One of issue in marriage is domestic violence. Data from the National Commission on Violence Against Women in 2023 (Komnas Perempuan), gender-based violence that occurred during 2022 experienced the most significant increase over the past 10 years, namely 339,782 cases. The report also states that gender-based violence is dominated by sexual and physical violence, namely 38. 21% of sexual violence and 35.72% of physical violence. Marital rape is sexual violence that occurs in a marital relationship. Based on data from the National Commission on Violence Against Women (Komnas Perempuan), there were 422 cases of sexual violence committed by husbands against their wives throughout 2022. In every type of violence, it does not escape the detrimental impact on the victim. The impact of violence is physical, psychological, sexual, economic, social, and legal. The purpose of this study was to explore community perceptions of the incidence of marital rape in the Jetis Health Center working area, Yogyakarta City. This research uses a qualitative research method with a descriptive analysis approach. Data collection was carried out using in-depth interviews. Participants totaled 11 people who were selected through purposive sampling and snowball methods.. The results of this study describe how people’s perceptions of marital rape include perceptions of the definition of marital rape, the impact, and perceptions of how domestic violence is handled in the area where they live.